DESIGN OF THE PRE-UNIVERSITY TRAINING BASED ON CDIO IDEOLOGY - Victoria I. Lyakh; Edward A. Rudnitskiy (Высшее образование в России)
The article proposes theoretical underpinning for the need of improvement pre-university level of education to implement an innovative approach to the training of engineers based on CDIO ideology. Pre-university training of enrollees is discussed as an initial step to improve the quality of engineering education. The reasons of enrollees' unpreparedness to choose engineering professions are analyzed. The paper proposes the possible solutions of the stated problem by means of specially organized educational process implemented by the university, secondary schools and/ or inter-school educational institutions of additional education. The implementation of CDIO standards in the design of pre-university training is discussed. The authors describe the experience in implementation of a specially organized course "Engineering" held for the pupils of 10-11 grades of Kirovsky district schools at Siberian Federal University in Krasnoyarsk in 2014-2015. The problems identified during the implementation of the course are revealed. The proposed solutions of the problems will allow to improve the educational process in the framework of the professional course "Engineering" and the quality of pre-university training level to implement an innovative approach to training of engineers in CDIO ideology.